Research Paper: Quantification of Mortality Rate From Illicit Substance Abuse in Iran in 2016 - Barzegar, Abdolrazagh; Shahbazi, Fatemeh; Mirtorabi, Davood; Ghadirzadeh, Mohammad Reza; Shojaei, Ahmad; Hashemi Nazari, Seyed Saeed (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: The present study aimed to evaluate the epidemiology of mortality due to substance abuse to provide useful information for local, national, and international administrators. Methods: This cross-sectional study was carried out in 12 months from March 2016 to February 2017. The study population was a random sample of people who died from substance abuse. Data were collected by checklists which were designed according to the study objectives. The obtained data were analyzed in Stata software. Results: Our findings show that the mortality rate for illicit opiate users was 40.90 per 1000000 population. Most deaths occurred among people aged 30 to 39 years (25%), single (46.75%) with low education levels. Kermanshah, Lorestan, and Alborz provinces had the highest mortality rate. History of overdose, suicide, hospitalization in psychiatric in hospital and incarceration was observed in some people who died from substance abuse. Conclusion: A large number of deaths from drug abuse occurred in unmarried, self-employed, young males 30 to 39 years old with low education levels. We suggest that training programs and harm reduction approaches be focused in these high risk groups.